miR-361-5p Mediates SMAD4 to Promote Porcine Granulosa Cell Apoptosis through VEGFA - Ma, Mengnan (Biomolecules, 2020)
Follicular atresia is an inevitable degenerative process that occurs in mammalian ovarian follicles. The molecular events involved in atresia, particularly granulosa cell apoptosis, have long attracted researchers’ attention. Vascular endothelial growth factor A (VEGFA) is downregulated during follicular atresia in porcine ovaries and serves as an inhibitor of apoptosis in granulosa cells. In addition, transforming growth factor (TGF)-βsignaling has been considered a central trigger in granulosa cell apoptosis. However, the link between TGF-β signaling and VEGFA is unknown. We proved that miR-361-5p is significantly upregulated during the atresia process and that it promotes GC apoptosis by directly targeting the VEGFA 3′UTR. In addition, we revealed that the miR-361-5p coding gene MIR361 was significantly downregulated by SMAD4, the central intracellular mediator of TGF-β signaling, that bound to the MIR361 promoter. In conclusion, our findings expanded what is known about VEGFA posttranscriptional regulation and revealed a complete SMAD4/miR-361-5p/VEGFA regulatory network in ovarian granulosa cell apoptosis. These data provide useful references for follicular atresia and ovarian physiological function studies.